Adsorption of Dye by Waste Black Tea Powder: Parameters, Kinetic, Equilibrium, and Thermodynamic Studies. (8th February 2020) - Lin, Dongyi; Wu, Fan; Hu, Yuqun; Zhang, Tingzhong; Liu, Chengshun; Hu, Qiangda; Hu, Yunfei; Xue, Zhihui; Han, Hua; Ko, Tzu-Hsing
Abstract : Waste black tea powder was used as a potential adsorbent to remove methylene blue (MB) from aqueous solution. Several operating factors in adsorption of MB onto waste black tea powder were investigated, including contact time, initial MB concentration, solution pH, adsorption temperature, and dosage of waste black tea powder. Experimental results revealed that the adsorption efficiency increased with contact time and solution pH values and decreased with initial MB concentration and adsorption temperature. The equilibrium time was estimated to be around 60 min. The maximum adsorption capacity and the highest adsorption efficiency were 302.63 mg·g −1 and 100%, respectively. In kinetic study, pseudo-first-order and pseudo-second-order kinetic models, intraparticle diffusion model, and Boyd and Elovich models were employed to analyze the adsorption behavior and the adsorption mechanism. It was found that the pseudo-second-order kinetic model was suitable to describe the adsorption process, and the calculated equilibrium adsorption capacity was well close to the experimental data for different initial MB concentrations. The internal diffusion was not the only rate-controlling step, and the existence of boundary effect was observed in this study. From isotherm analysis, the equilibrium data were well represented by the Langmuir model, rather than Freundlich, Dubinin–Redushckevich, or Temkin models. The nonlinear fitting for various isotherm models implied that the adsorption behavior between MB and waste black tea powder was complication. Thermodynamic parameters including changes in Gibb's free energy, enthalpy, and entropy suggested that adsorption of MB onto waste black tea powder was a spontaneous and exothermic process. The multiple regeneration/adsorption experiments indicated that the used black tea powder efficiently remained more than 75% after five cycles using NaOH as a regenerative reagent and thus be used for many times. Therefore, as a low-cost and easily available material, waste black tea powder could be applied in wastewater treatment.